Factors Associated with Mortality in Patients with Autoimmune Diseases Admitted to the Intensive Care Unit in Bogota, Colombia - Carrizosa, Jorge Armando; Aponte, Jorge; Cartagena, Diego; Cervera, Ricard; Ospina, Maria Teresa; Sanchez, Alexander (Frontiers in Immunology, 2017)
Patients with autoimmune diseases (ADs) are a challenge for the intensivist; it is hard to differentiate among infection, disease activity, and combinations of both, leading to high mortality. This study is a retrospective analysis of 124 critically ill patients admitted to the intensive care unit (ICU) in a university hospital between 2008 and 2016. Bivariate case–control analysis was performed, using patients who died as cases; later, analysis using a logistic regression model with variables that were associated with mortality was conducted. Four variables were consistently associated with mortality in the logistic regression model and had adequate prediction value (Hosmer and Lemeshow statistic = 0.760; Nagelkerke R-squared = 0.494). The risk of death was found to be statistically associated with the following: shock at admission to ICU [odds ratio (OR): 7.56; 95% confidence interval (CI): 1.78–31.97, p = 0.006], hemoglobin level <8 g/dL (OR: 16.12; 95% CI: 3.35–77.52, p = 0.001), use of cytostatic agents prior to admission to the ICU (OR: 8.71; 95% CI: 1.23–61.5, p = 0.03), and low levels ofcomplement C3 (OR: 5.23; 95% CI: 1.28–21.35, p = 0.02). These variables can guide clinicians in the early identification of patients with AD with increased risk of death during hospitalization, leading to initial therapies seeking to improve survival. These results should be evaluated prospectively in future studies to establish their predictive power.